Comparison of two power densities on the healing of palatal wounds after connective tissue graft removal: randomized clinical trial - da Silva Neves, Felipe Lucas [UNESP]; Silveira, Camila Augusto [UNESP]; Dias, Stephanie Botti Fernandes [UNESP]; Santamaria Júnior, Milton; de Marco, Andrea Carvalho [UNESP]; Kerbauy, Warley David [UNESP]; de Melo Filho, Antonio Braulino [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Springer Nature, 2016)
Connective tissue graft (CTG), which is considered to be among the best techniques for treating gingival recession, has presented stable long-term results. However, this technique causes morbidity and discomfort in the palatine region due to graft removal at that site. A previous study reports that photobiomodulation (PBM) using a dosage of 15 J/cm2 may improve wound healing and the patient’s postoperative comfort. However, no other studies in the literature provide the best application dosage or comparisons between protocols for this purpose. The aim of this study is to compare two power densities of PBM on the wound-healing process of the donor palatine area after CTG removal. In this study, 51 patients presenting buccal gingival recession were randomized into one of the following groups: group 1: CTG procedure for root coverage and PBM application at the donor site using a 60 J/cm2 dose; group 2: CTG and PBM application using a 30 J/cm2 dose; or group 3: CTG and sham application. The evaluated parameters were the wound remaining area (WRA), scar and tissue colorimetry (TC), tissue thickness (TT), and postoperative discomfort (D), evaluated at baseline and 7, 14, 45, 60, and 90 days after surgery. Group 1 presented statistically significant smaller wounds at day 7 (p > 0.05). None of the patients presented scars at the operated area, and all of the patients reported mild discomfort, with low consumption of analgesic pills. We concluded that the protocol of 60 J/cm2 provided faster wound healing 7 days after removing the connective tissue graft for root coverage. Trial registration: ClinicalTrial.org (NCT02580357) https://clinicaltrials.gov/ct2/show/NCT02580357.
Keywords: Connective tissue graft; Gingival recession; Low-level laser therapy; Wound healing